Inovasi Berkelanjutan Limbah Musa Paradisiaca L. untuk Meningkatkan Green Entrepreneurship - Nurhidayah, Indah; Meishanti, Ospa Pea Yuanita; Amburika, Nudiya; Chasanah, Novi Zahrotul (EDUSCOPE: Jurnal Pendidikan, Pembelajaran, dan Teknologi, 2024)
ABSTRACT Banana is a versatile plant that is utilized from the roots to the skin, which is usually processed into banana chips in the home industry. However, the increase in banana chip production has caused an increase in banana peel waste that is disposed of without optimal utilization. This causes negative environmental impacts such as bad odors. Therefore, innovation and awareness are needed to manage banana peel waste sustainably in order to reduce negative impacts on the environment and create value-added products that encourage the development of Green entrepreneurship. This study aims to utilize banana peel waste as a raw material in the production of organic bar soap. The method applied is by using a workshop (training). Training in making organic soap from kepok banana peel waste is designed to strengthen the spirit of sustainable entrepreneurship among students of KH. A. Wahab Hasbullah University. The results of this study provide a significant contribution to improving Green entrepreneurship practices through sustainable innovation in utilizing kepok banana peel waste into organic bar soap. By adopting the concept of making organic bar soap, researchers can not only reduce the negative impact of banana peel waste on the environment, but also create quality products. Organic bar soap has the potential to meet consumer demand who are increasingly concerned with natural and sustainable products. KEYWORDS: banana peel, green entrepreneurship, sustainable innovation, organic soap ABSTRAK Pisang merupakan tanaman serbaguna yang dimanfaatkan dari akar hingga kulitnya, yang biasanya diolah menjadi keripik pisang dalam industri rumahan. Namun, peningkatan produksi keripik pisang menyebabkan peningkatan limbah kulit pisang yang dibuang tanpa pemanfaatan optimal. Hal ini menyebabkan dampak lingkungan negatif seperti bau busuk. Oleh karena itu, perlu inovasi dan kesadaran untuk mengelola limbah kulit pisang secara berkelanjutan guna mengurangi dampak negatif terhadap lingkungan dan menciptakan produk bernilai tambah yang mendorong perkembangan Green entrepreneurship. Penelitian ini bertujuan memanfaatkan limbah kulit pisang sebagai bahan baku dalam produksi sabun batang organik. Metode yang diterapkan adalah dengan menggunakan workshop (pelatihan). Pelatihan pembuatan sabun organik dari limbah kulit pisang kepok, dirancang untuk memperkuat semangat kewirausahaan berkelanjutan di kalangan mahasiswa Universitas KH. A. Wahab Hasbullah. Hasil penelitian ini memberikan kontribusi yang signifikan dalam rangka peningkatan praktik Green entrepreneurship melalui inovasi berkelanjutan dalam pemanfaatan limbah kulit pisang kepok menjadi sabun batang organik. Dengan mengadopsi konsep pembuatan sabun batang organik, para peneliti tidak hanya dapat mengurangi dampak negatif limbah kulit pisang terhadap lingkungan, tetapi juga menciptakan produk yang berkualitas. Sabun batangan organik berpotensi memenuhi permintaan konsumen yang semakin peduli dengan produk alami dan berkelanjutan. KATA KUNCI: kulit pisang, green entrepreneurship, inovasi berkelanjutan, sabun organik